2015
DOI: 10.1039/c4dt02719a
|View full text |Cite
|
Sign up to set email alerts
|

Core substituted naphthalene diimide – metallo bisterpyridine supramolecular polymers: synthesis, photophysics and morphology

Abstract: A series of metallo Ru(ii), Fe(ii), Co(ii) bisterpyridine polymers were prepared with naphthalene diimide (NDI) groups inserted between two 4'-phenyl-2,2:6',2''-terpyridine (phtpy) groups. Core-substituted NDIs typically have long-lived excited states with relatively high quantum yields, yet the NDI emission in these metallopolymers was completely quenched, most likely because of efficient electron-transfer from the M(phtpy)2(2+) groups to the excited NDIs. AFM, TEM and SEM experiments indicate that the regioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…The MLCT band of the [Fe 2+ (s-tpy) 2 ] complex where pyr and ph-tpy moieties of the ligand are connected through a nonconjugated single-bond linker appears at 568 nm, identical to the previously reported MLCT band of [Fe 2+ (ph-tpy) 2 ] centered at 568 nm. 53 Moreover, N-methylation of the pyr moiety has no influence on the MLCT band of [Fe 2+ (CH 3 -stpy) 2 ]I 2 (BF 4 ) 2 observed at 568 nm. On the contrary, the introduction of a conjugated linker leads to a red shift of the MLCT bands of [Fe 2+ (d-tpy) 2 ](BF 4 ) 2 and [Fe 2+ (t-tpy) 2 ]-(BF 4 ) 2 to 574 nm.…”
Section: Uv−vis Absorption Of Ligands and Complexes Inmentioning
confidence: 96%
“…The MLCT band of the [Fe 2+ (s-tpy) 2 ] complex where pyr and ph-tpy moieties of the ligand are connected through a nonconjugated single-bond linker appears at 568 nm, identical to the previously reported MLCT band of [Fe 2+ (ph-tpy) 2 ] centered at 568 nm. 53 Moreover, N-methylation of the pyr moiety has no influence on the MLCT band of [Fe 2+ (CH 3 -stpy) 2 ]I 2 (BF 4 ) 2 observed at 568 nm. On the contrary, the introduction of a conjugated linker leads to a red shift of the MLCT bands of [Fe 2+ (d-tpy) 2 ](BF 4 ) 2 and [Fe 2+ (t-tpy) 2 ]-(BF 4 ) 2 to 574 nm.…”
Section: Uv−vis Absorption Of Ligands and Complexes Inmentioning
confidence: 96%
“…The NDI emission in these metallopolymers was completely quenched, which may be due to an efficient electron transfer from the M­(phtpy) 2 2+ groups to the excited states of NDIs. SEM and TEM analysis clearly shows the formation of bundled nanorods with lengths of the order of ∼8 μm . Liu et al reported the syntheses and structures of three isostructural 1D NDI based supramolecular coordination networks, and upon the lone pair−π interactions between the capped halogen atoms and electron-deficient NDI, furthermore, the NDI based coordinated network exhibited different photochromic behaviors upon photoiradiation …”
Section: Supramolecular Self-assemblymentioning
confidence: 99%
“…Modarelli and co-workers reported bisterpyridine-functionalized cNDI derivatives (10 and 11, Figure 4) that formed extended supramolecular polymers in the presence of different divalent metal ions (Ru 2þ , Fe 2þ and Co 2þ ). 13 The typical high-emissive cNDI monomers exhibited negligible fluorescence in its metallo-supramolecular polymeric state due to electron transfer from the metal ions to the NDI moiety via the bridging ligands in the excited state. 13 George and co-workers demonstrated supramolecular polymerizations of two β-sheet forming peptide-tethered amphiphilic cNDI derivatives (12 and 13) and their pHresponsive behaviour (Figure 5).…”
Section: General Supramolecular Assemblies Of Cndi Derivativesmentioning
confidence: 99%
“…13 The typical high-emissive cNDI monomers exhibited negligible fluorescence in its metallo-supramolecular polymeric state due to electron transfer from the metal ions to the NDI moiety via the bridging ligands in the excited state. 13 George and co-workers demonstrated supramolecular polymerizations of two β-sheet forming peptide-tethered amphiphilic cNDI derivatives (12 and 13) and their pHresponsive behaviour (Figure 5). 14 One of the cNDI building blocks (12) was symmetrically functionalized with the diethoxy groups in the aromatic core, while the other one ( 13) was unsymmetrically substituted with isopropylamine and ethoxy groups.…”
Section: General Supramolecular Assemblies Of Cndi Derivativesmentioning
confidence: 99%
See 1 more Smart Citation